Analisis Hukum Islam dan Hukum Positif Terhadap Suami yang Menghamili Adik Kandung Istri: Studi Kasus Desa Mbawi Kab. Dompu - Yadin Tri Putra; Muhammad Aminullah; Muh. Yunan Putra (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine the views of Islamic law and positive law on husbands who impregnate their wives' younger siblings, and to find out the position of children born from the husband's relationship with his wife's younger siblings according to Islamic law and positive law in Indonesia. This research uses descriptive qualitative methods to understand social phenomena in depth. With this approach, researchers can collect accurate and factual descriptive data about observed behavior and social interactions. Qualitative methods allow researchers to gain a more complex and complete insight into the phenomenon under study, so as to provide a clearer and more comprehensive picture of the observed social reality. This research uses primary and secondary data. Primary data is collected directly from the original source, while secondary data comes from supporting literature. Data collection methods include observation, interviews, and document studies. Data analysis was conducted systematically to produce accurate and comprehensive findings. This study concludes that both Islamic law and Indonesian positive law prohibit and sanction the actions of husbands who impregnate their wives' younger siblings, with severe legal consequences in the perspective of Islamic law and criminal sanctions in positive law. Children born from this forbidden relationship have a special status, namely only having a nasab relationship with their mother and not having the same rights as legitimate children, both in Islamic law and Indonesian positive law. Therefore, it is important for the community to understand the legal and social consequences of these illicit relationships and protect the rights of children born in these conditions.